Regulation of melanogenesis in conditionally immortalised mouse melanocytes expressing a temperature-sensitive SV40 large T antigen - Prince, Sharon (Division of Cell Biology, 2018)
The transformation of a normal melanocyte to a malignant melanoma involves a series of poorly understood genotypic and phenotypic alterations. In vitro models of melanoma formation generated by transforming mouse melanocytes with exogenous oncogenes have revealed that this process is frequently accompanied by a loss of pigmentation. The aim of this study was to establish, and to make use of unique cell lines to gain further insight into the mechanism(s) by which oncoproteins alter melanocyte differentiation. Primary cultures of mouse epidermal and dermal melanocytes were infected with a retrovirus carrying a temperature-sensitive mutant SV40 large T antigen. Six immortalised cell lines thus generated were analysed by northern and western blots and by enzymatic assays at the permissive temperature of the oncoprotein. Three epidermal and two dermal melanocyte clones remained pigmented and expressed tyrosinase, TRP-1 and -2 genes and the proteins encoded by them. In addition they expressed the mi gene and the c-kit receptor. In contrast, one dermal melanocyte clone (DMEL-3) gradually depigmented: this was accompanied by enhanced growth and down-regulation of melanocyte-specific gene expression. At the non-permissive temperature of the oncoprotein, proliferation ceased and DMEL-3 cells repigmented with a time-dependent increase in melanocyte-specific gene expression. Moreover, mi gene expression was down-regulated in the DMEL-3 cell line at the permissive temperature and was re-expressed at the non-permissive temperature. These results provided direct evidence for the role of the SV40 large T antigen in melanocyte dedifferentiation and emphasized the pivotal role of Mi in this process. Northern blot analysis of DMEL-3 cells cultured at the permissive and non-permissive temperatures revealed that there were no detectable levels of Pax3 transcripts at either temperature. In addition, Pax3 expression was absent in the highly pigmented DMEL-2 and melan-a cell lines. These results suggest that Pax3 is not required for mi expression and that it is unlikely to be a target of the T antigen-mediated repression of mi. To explore the possibility that other melanocyte markers are also altered as a consequence of alterations in mi expression, the DMEL-3 cells were examined for changes in the α-MSH and c-kit receptors. Melanin synthesis and tyrosinase activity assays showed that alterations in mi expression did not correlate to responsiveness to α-MSH, suggesting that the MSH receptor gene is not regulated by Mi. Furthermore, northern blot analysis showed that DMEL-3 cells did not express c-kit at either the permissive or nonpermissive temperature, suggesting that Mi does not regulate c-kit expression. To address the possible role of RB family members in melanocyte differentiation, it was investigated whether melanocyte differentiation is accompanied by an increase in their mRNAs and protein levels. Northern blot analysis strongly suggested that expression of the RB1, p130 and p107 is not altered when DMEL-3 cells were induced to differentiate at the non-permissive temperature. The results from western blot anaysis were inconclusive and require further investigations. Finally, the pigmented cell lines established in the present study provided a unique opportunity to investigate the stimulatory effect of TPA on melanogenesis because growth curves showed that the cells become TPA-independent. The results showed that stimulation of melanogenesis by TPA in a pigmented melanocyte line, DMEL-2, resulted in an increase in tyrosinase, TRP-1 and TRP-2 proteins and mRNAs. Additionally, TPA increased mi gene expression which suggests that Mi is necessary for the TPA-triggered signalling cascade that induces expression of the tyrosinase gene family. These results disclose, for the first time, a mechanistic link between TPA and the transcriptional induction of pigmentation.